2020
DOI: 10.3324/haematol.2019.237719
|View full text |Cite
|
Sign up to set email alerts
|

Targeted genotyping of circulating tumor DNA for classical Hodgkin lymphoma monitoring: a prospective study

Abstract: The relevance of circulating tumor DNA (ctDNA) analysis as a liquid biopsy and minimal residual disease tool in the management of classical Hodgkin Lymphoma (cHL) patients was demonstrated in retrospective settings and remains to be confirmed in a prospective setting. We developed a targeted Next-Generation sequencing (NGS) panel for fast analysis (AmpliSeq® technology) of nine commonly mutated genes in biopies and ctDNA of cHL patients. We then conducted a prospective trial to assess ctDNA follow up at diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 20 publications
5
59
0
Order By: Relevance
“…Concerning the burden parameters, TMTV was found to be significantly correlated with [cfDNA] and [ctDNA] levels in both DLBLC and cHL, as already found in previous studies [15,16]. We have also found that TMTS was frequently among the more highly correlated parameters with cfDNA and ctDNA levels (among the three first parameters in 2 cases of 4).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Concerning the burden parameters, TMTV was found to be significantly correlated with [cfDNA] and [ctDNA] levels in both DLBLC and cHL, as already found in previous studies [15,16]. We have also found that TMTS was frequently among the more highly correlated parameters with cfDNA and ctDNA levels (among the three first parameters in 2 cases of 4).…”
Section: Discussionsupporting
confidence: 88%
“…Thirty patients with diffuse large B cell lymphoma (DLBCL) and 50 patients with classical Hodgkin lymphoma (cHL) were enrolled prospectively. Description of the population with clinical characteristics and outcomes is available in two previous studies [15,16]. All patients had performed a PET/CT on one of 3 different machines (description summarized in Additional file 1: Table 1).…”
Section: Patientsmentioning
confidence: 99%
See 3 more Smart Citations